Performance of rice (Oryza sativa) cultivars as influenced by irrigation regimes and establishment methods - BRAR, A S; KAUR, KULJIT; SHARMA, RAJNI; SINDHU, V K (The Indian Journal of Agricultural Sciences, 2021)
The present study was carried out at Punjab Agricultural University, Ludhiana during kharif 2016 and 2017 to compare economics, energetics, crop and water productivity of rice (Oryza sativa L.) cultivars grown under variable irrigation regimes and crop establishment methods. Results revealed that the rice variety PR 126 produced 22.6 and 23.3% higher grain yield than PR 115 and PR 124, respectively. Scheduling irrigation at 2 days after infiltration of ponded water (DAIPW) in puddled transplanted rice (PTR) resulted in highest grain yield (7.07 t/ha), which was statistically similar to irrigation at 3 DAIPW in PTR (6.96 t/ha), but significantly higher than direct seeded rice (DSR) irrigated at 2, 4, 6 and 8 DAIPW. The interaction between cultivars and establishment-irrigation regimes showed that PR 126 performed statistically equal under PTR and DSR conditions at all irrigation regimes except 6 and 8 DAIPW. However, maximum net returns and B:C was obtained from PR 126 when puddled transplanted and irrigated at 2 DAIWP. PR 124 irrigated at 2 DAIPW in PTR consumed maximum amount of irrigation water (130.3 cm). Compared to that, PR 126 when direct seeded and irrigated at 4 DAIPW saved 42.8 cm of irrigation water and registered 43, 30.2, 6.6 and 6.3% higher apparent crop water productivity, total crop water productivity, energy use efficiency and energy productivity, respectively with statistically similar grain yield and B:C.